Enhancing mental health literacy in obsessive-compulsive disorder and reducing stigma via smartphone: A randomized controlled trial protocol - Antonio Chaves; Sandra Arnáez; Diana Castilla; María Roncero; Gemma García-Soriano (Internet Interventions, 2022)
Background: Obsessive-compulsive disorder (OCD) is a disabling disorder that can be successfully treated. However, individuals with OCD do not seek or delay seeking treatment. This delay may be explained by poor mental health literacy and stigmatizing attitudes toward OCD in community. In order to work on these variables, a gamified mental health mobile application (app) called esTOCma has been developed. The purpose of this study is to describe the protocol for a study to test the efficacy of esTOCma, increasing mental health literacy and help-seeking intention, reducing the stigmatizing attitudes and social distance suffered by people with OCD, as well as the distress associated with obsessive-compulsive symptoms. Methods: A randomized controlled trial with a crossover design with two conditions (immediate-use App group versus delayed-use App group) will be conducted on a non-clinical adult sample of the community of a minimum size of 200 participants. Participants in the immediate-use App group will start using the app at baseline until completion (10 days); whereas participants in the delayed-use App group will wait 10 days, and then start using the app until completion (10 days). The outcomes will be measured at four assessment points (baseline; 10 days from baseline; and 20 days from baseline; and after 3 months). The following instruments will be administered: Attribution Questionnaire, General Help-Seeking Questionnaire, Social Distance Scale, Mental Health Literacy, Psychoeducation Questionnaire, Social Desirability Scale, Single-Item Self-esteem Scale, and Obsessive-Compulsive Inventory-Revised. Discussion: This protocol presents the first study to describe a randomized control trial of a mental health app focused on changing mental health literacy, stigmatizing attitudes, social distance and help-seeking intention associated with OCD. An app intervention of these characteristics is especially relevant nowadays as the COVID-19 pandemic has increased obsessive-compulsive symptoms and severity. An improvement in general knowledge about OCD and a reduction in stigma could be associated with earlier OCD detection and an increase in help-seeking intention, which could result in greater wellbeing. Moreover, normalizing intrusions and knowledge about the cognitive OCD model could serve as a protective variable in vulnerable individuals. Trial registration: ClinicalTrials.gov identifier: NCT04777292. Registered February 23, 2021, https://clinicaltrials.gov/ct2/show/NCT04777292.